Capturing systematically users' experience of evaluation tools for integrated AMU and AMR surveillance - Alban, Lis; Bordier, Marion; Häsler, Barbara; Collineau, Lucie; Tomassone, Laura; Bennani, Houda; Aenishaenslin, Cécile; Norström, Madelaine; Aragrande, Maurizio; Filippitzi, Maria Eleni; Moura, Pedro; Sandberg, Marianne (Frontiers in Veterinary Science, 2023)
Tackling antimicrobial resistance (AMR) is a goal for many countries. Integrated surveillance of antimicrobial use (AMU) and resistance is a prerequisite for effective risk mitigation. Regular evaluation of any surveillance is needed to ensure its effectiveness and efficiency. The question is how to evaluate specifically integrated surveillance for AMU and AMR. In an international network called CoEvalAMR, we have developed guidelines for selection of the most appropriate tools for such an evaluation. Moreover, we have assessed different evaluation tools as examples using a country case format, using a methodology with a focus on the user’s experience. This paper describes the updated methodology, which consists of a brief introduction to the case and to the tool separately. Moreover, there are 12 functional aspects and nine content themes which should be scored using a 4-tiered scale. Additionally, four Strength, Weakness, Opportunities, Threat (SWOT) questions should be addressed. Results are illustrated using radar diagrams. An example of application of the updated methodology is given using the ECoSur evaluation tool. No tool can cover all aspects, so the choice of tool must be based upon the specific evaluation purpose and adequate resources, time and training are needed for obtaining useful output from the evaluation. Our updated methodology can be used by tool users to share their experience with available tools , and hereby assist other users in identifying the most suited tool for their evaluation purpose. Moreover, the tool developers can get valuable information for further improvements of their tool.